Effects of Anterior Borderzone Angle Grading on Predicting the 90-Day Prognosis After Recanalization of Acute Middle Cerebral Artery Occlusion - Chen, Ying; Hong, Quanlong; Liu, Junpeng; Zheng, Zhen; He, Yingchao; Chen, Shuheng; Wang, Canxiong; Cai, Mengjuan; Cheng, Qiong; Wang, Yinzhou; Li, Yongkun (Frontiers in Neurology, 2021)
Objective: This work explores collateral circulation metrics, such as the anterior borderzone angle grading (ABZA-grading), as a predictor of the prognosis in patients with acute middle cerebral artery occlusion (MCAO) following endovascular treatment (EVT). Methods: Clinical data from 108 patients with acute MCAO, treated by EVT, were retrospectively analyzed. In patients with MCAO, ABZA is the angle between the median line of the sagittal sinus and the boderzone of the pial arterioles of ACA and MCA, and the ABZA/23.0° was rounded to obtain the corresponding collateral circulation score (ABZA-grading). In parallel, the primary outcome was defined as the 90-day clinical outcome by modified ranking scale score (mRS). Univariate analysis and logistic regression were used to analyze the independent predictors of the 90-day clinical outcome (mRS). Receiver operating characteristic curve (ROC) analysis was used to judge the predictive value of ABZA. Results: Univariate analysis and logistic regression analysis showed that a decrease in NIHSS(National institute of health stroke scale) >4, ABZA-grading >2 and with severe complications were independent predictors of the 90-day clinical outcome after EVT in patients with acute MCAO. The ROC analysis showed that ABZA alone could predict a favorable 90-day clinical outcome with an area under the curve (AUC) of 0.868. Using an ABZA of >57.8° (the corresponding ABZA-grading of >2) as the cut-off value, the predictive sensitivity and specificity of 75.7% and 88.7% respectively. Contingency table analysis showed a statistical difference in mRS score between ABZA-grading subgroups，and ABZA-grading between stroke caused by large artery atherosclerosis (LAA) and cardiogenic embolism (CE). Conclusion: The ABZA-grading is an easy and objective assessment of collateral circulation that can predict short-term clinical outcome after EVT in patients with acute MCAO. Therefore, it may guide selection of patients with acute ischemic stroke (AIS) suitable for EVT. The ABZA-grading of collateral circulation can be a supplemental metrics to help differentiate stroke by LAA and CE.